ON THE STUDY OF SOMATIC CODS (Scientific journal of the Fergana State University, 2023)
The modern direction of linguistics in quality, the main attention of linguoculturology is paid to the study of cultural codes. Cultural codes-act as the key in increasing the national-cultural image of a particular people. The following will analyze the study of the somatic code and the meaning it represents, as well as their main characteristics.